Santa Maria Ratu Rosari Parish Information System Tanjung Selamat Medan - Sitorus, Lamhot; Purba, Vinny Yana Laurenta Br (UNIKA Santo Thomas, 2021)
The church is an organization engaged in community service. The church also has an information management system including the management, storage, and presentation of data. The service management system of the Santa Maria Ratu Rosari Parish Tanjung Selamat Medan is still manual which causes ineffective and efficient services. The purpose of this research is to design a web-based service management information system for members of the congregation to support every church service activity to the people. The system design method used is the Waterfall method with the design model using Unified Modeling Language (UML) diagrams. The results of the system design in this study display information about the church and its servants, information on church activities, people, articles, registration services for members of the congregation, registration data reports presented in graphic form, as well as the management of all congregational data and church data.